Photolytic release at different wavelengths of tetrapeptide AAPV from a pyrenylmethyl conjugate - Santos, Filipa C. (2015)
Comunicação em painel no 2nd Symposium on Medicinal Chemistry, Braga, Portugal, 8 Maio 2015